Transient Antidiuretic Hormone Insufficiency Caused by Severe Hyperosmolar Hyperglycemic Syndrome Based on Nephrogenic Diabetes Insipidus - Mizuki Gobaru, MD (Elsevier, 2021)
Background: The hyperosmolar hyperglycemic state (HHS), an acute complication of diabetes mellitus with plasma hyperosmolarity, promotes the secretion of anti-diuretic hormone (ADH) and reduces the storage of ADH. Magnetic resonance T1-weighted imaging reflects ADH storage in the posterior pituitary lobe, which disappears when the storage is depleted. Whether the HHS induces ADH depletion leading to clinical manifestations has been unclear. Case Report: A 55-year-old Japanese woman was admitted to our center because of mental disturbance and hypotension. She had received lithium carbonate for bipolar disorder and presented with polydipsia and polyuria from 15 years of age. On admission, she had mental disturbance (Glasgow Coma Scale, E4V1M1), hypotension (systolic blood pressure, 50 mmHg), and tachycardia (pulse rate, 123/min). Plasma glucose was 697 mg/dL osmolality was 476 mOsm/kg•H2O, and bicarbonate was 23.7 mmol/L. The diagnoses of HHS and hypovolemic shock were made. During treatment with fluid replacement and insulin therapy, the urine volume continued to be approximately 3 to 4 L/day, and an endocrine examination revealed ADH insufficiency and nephrogenic diabetes insipidus. Desmopressin 10 μg/day and trichlormethiazide 2 mg/day were necessary and administered, and the endogenous ADH secretion improved gradually. The signal intensity of the pituitary posterior lobe, initially decreased on magnetic resonance T1 images, was also improved. Conclusion: This patient had ADH insufficiency associated with ADH depletion due to hyperosmolarity and nephrogenic diabetes insipidus. Clinicians should be aware of the risk of the development of critical HHS and relative ADH insufficiency in patients being treated with lithium carbonate.